Hubungan Spiritualitas Dan Lama Perawatan Dengan Kecemasan Keluarga Pasien Intensive Care Unit (ICU) RSI Aisyiyah Malang - Munawaroh; Widodo, Dyah; Marsaid; Bahari, Kissa (Jurnal Keperawatan Muhammadiyah, 2024)
Objective: To investigate the association between spirituality and length of treatment with family anxiety among Intensive Care Unit (ICU) patients at RSI Aisyiyah Malang. Methods: The research design uses non-experimental quantitative methods with a cross-sectional correlation approach. The sampling method used total sampling, namely all families and patients of the Intensive Care Unit (ICU) of RSI Aisyiyah Malang totaling 33 respondents Results: The study's findings indicated that the patient's family's spiritual level was generally high, the average length of patient care was 4 days, and the patient's family's anxiety level was relatively low. The Spearman rank correlation test results revealed a p-value of 0.000 for the variables spirituality and length of therapy in connection to the patient's family's worry. Conclusion: The conclusion is that there is a relationship between spirituality and length of treatment with family anxiety of Intensive Care Unit (ICU) patients at RSI Aisyiyah Malang. It is hoped that hospitals, especially nurses, will pay attention in nursing care to the importance of spirituality in overcoming the anxiety of families of Intensive Care Unit (ICU) patients.